Charge Accumulation and Multi‐Electron Photoredox Chemistry with a Sensitizer–Catalyst–Sensitizer Triad. Issue 53 (27th August 2018) - Nomrowski, Julia; Guo, Xingwei; Wenger, Oliver S.
Abstract: Photoinduced electron transfer in donor–sensitizer–acceptor compounds usually leads to simple electron–hole pairs, and photoredox catalysis typically relies on single‐electron transfer (SET) events. This work reports on a molecular triad able to accumulate two electrons on a central dibenzo[1, 2]dithiin moiety flanked by two peripheral Ru II photosensitizers. Under continuous illumination, the doubly reduced form of the dibenzo[1, 2]dithiin undergoes thiolate–disulfide exchange with an aliphatic disulfide substrate, thereby acting as a two‐electron catalyst after two initial SET events with triethylamine at the Ru II sensitizers. The use of a relatively simple triad for coupling two separate SET processes to a subsequent two‐electron reduction is an important conceptual advance from photoinduced SET and light‐driven charge accumulation towards multi‐electron photoredox catalysis. This is relevant for artificial photosynthesis and light‐driven multi‐electron chemistry in general. Abstract : Photoinduced multi‐electron transfer is made applicable to catalysis of an organic transformation, illustrating the usefulness of covalent sensitizer–catalyst constructs for initial charge accumulation followed by organic multi‐electron photoredox chemistry.